Tren Teknologi Masa Depan dan Tantangan Bagi Umat Islam dalam Perspektif Etika dan Syariah - Nadhira Aulia Mahira (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The purpose of this study is to examine future technological trends, including artificial intelligence, cryptocurrency, and biotechnology, along with the challenges they pose to Muslims from ethical and sharia perspectives. This research is considered significant in addressing the contemporary legal gap caused by the rapid pace of digital disruption. The study employs a qualitative method based on library research. Data were collected from scholarly articles, technology journals, fiqh literature, and fatwa documents, then analyzed through a normative-theological approach combined with the framework of Maqashid al-Shariah. The findings indicate that, according to the principle of al-ashlu fil asyya’ al-ibahah (the original ruling of things is permissibility), future technologies are generally considered permissible as tools or means. Artificial intelligence is not regarded as a legal subject (mukallaf), meaning that full responsibility remains in human hands. Cryptocurrency may be considered lawful when supported by real economic activities, but it becomes prohibited when it merely involves speculation or elements of maysir (gambling). Furthermore, gene editing is permissible when intended for medical treatment (tadawi), yet forbidden if aimed at altering God’s creation (taghyir khalqillah). The implications of this study may serve as a reference for fatwa institutions in formulating a more proactive digital fiqh, while also guiding Muslim technocrats in developing sharia-compliant technologies based on the priority needs of society. The uniqueness of this research lies in its integration of three major future technologies within a single Maqashid al-Shariah analytical framework presented in a practical, comprehensive, and accessible manner.